2022
DOI: 10.1186/s12904-022-01038-8
|View full text |Cite
|
Sign up to set email alerts
|

Communication of palliative care needs in discharge letters from hospice providers to primary care: a multisite sequential explanatory mixed methods study

Abstract: Background The provision of palliative care is increasing, with many people dying in community-based settings. It is essential that communication is effective if and when patients transition from hospice to community palliative care. Past research has indicated that communication issues are prevalent during hospital discharges, but little is known about hospice discharges. Methods An explanatory sequential mixed methods study consisting of a retros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 50 publications
0
0
0
1
Order By: Relevance
“…Unsere Ergebnisse decken sich zu großen Teilen mit ähnlichen Studien im palliativen Kontext. Diese konnten ebenfalls das regelmäßige Fehlen von relevanten Informationen in den Entlassdokumenten nachweisen und empfehlen Richtlinien zur Implementierung dieser Daten [27,28]. Da diese Dokumente derzeit häufig von Ärzt:innen in jungen Stadien ihrer Ausbildung verfasst werden, sollte bei der Verbesserung auch curricularen Faktoren während der universitären Ausbildung eine entscheidende Bedeutung zukommen [29].…”
Section: Inhalte Derunclassified
“…Unsere Ergebnisse decken sich zu großen Teilen mit ähnlichen Studien im palliativen Kontext. Diese konnten ebenfalls das regelmäßige Fehlen von relevanten Informationen in den Entlassdokumenten nachweisen und empfehlen Richtlinien zur Implementierung dieser Daten [27,28]. Da diese Dokumente derzeit häufig von Ärzt:innen in jungen Stadien ihrer Ausbildung verfasst werden, sollte bei der Verbesserung auch curricularen Faktoren während der universitären Ausbildung eine entscheidende Bedeutung zukommen [29].…”
Section: Inhalte Derunclassified
“…hospices), which is not only for people in the last days of life, but is available to intervene and support people with life-limiting illnesses whenever they develop complex palliative needs [ 2 4 ]. Patients who have benefited from specialist intervention during periods of acute/complex palliative care needs often transition from specialist-to-primary care where their day-to-day healthcare needs will be managed by general practice and community teams, once such needs have been managed and/or controlled [ 5 ]. A previous systematic review on hospice discharge [ 6 ] estimated discharge rates from 5–23%.…”
Section: Introductionmentioning
confidence: 99%
“…Our recent study looking at hospice discharge in five UK hospices, indicated that hospice patients (and where relevant, their carers) are not consistently receiving or being offered discharge letters [ 5 ]. Although hospice care seeks to provide a holistic service, we also found that there was a focus on physical needs in these letters, with much less focus on psychological/emotional and social needs, with spiritual needs being rarely documented (2.4%) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations